Optically Switched Frequency for Reconfigurable Dipole Antenna Using Photodiode Switches - Erna Risfaula Kusumawati; Yono Hadi Pramono; Agus Rubiyanto (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
The design, fabrication, and measurement of reconfigurable antenna using photodiode switches has been investigated. The antenna had dimension 104 mm x 41 mm x 1.6 mm and FR4 substrate with relative permittivity4.8. It structure was Coplanar Stripline (CPS) dipole. Two photodiodeshad assembled on gap in both dipole arms, which was activated by 600 nm red laser. The unilluminated state, antennahad resonant frequency 800 MHz with RL -32 dB, 2225 MHz with RL -12.5 dB, 3320 with RL -14.1 dB. Meanwhile for the illuminated state, antennahad resonant frequency and return loss shifting to 800 MHz with RL -32 dB, 2225 MHz with RL -12.5 dB, 3320 MHz with RL -14.1 dB.This condition caused low impedance and longer dipole arm. If dimension size increases, resonant frequency will decrease. So, there was shifting frequency and return loss at under illuminated by laser.